2004
DOI: 10.1086/502466
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Serratia marcescens Outbreaks in Two Neonatal Intensive Care Units

Abstract: S. marcescens causes significant morbidity and mortality in preterm neonates. Cross-transmission via transient hand carriage of a HCW appeared to be the probable route of transmission in NICU A. Sinks did not harbor the outbreak strains. Antimicrobial susceptibility patterns did not prove to be an accurate predictor of strain relatedness for S. marcescens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0
2

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 13 publications
3
28
0
2
Order By: Relevance
“…In Brazil, resistance to carbapenems in S. marcescens strains has rarely been reported and is associated exclusively with KPC-2 production (4,5,18). Outbreaks of S. marcescens infections in ICUs are frequently associated with considerable mortality rates, ranging from 14% to 60% (18,19). This observation is in accordance with our findings, as the overall mortality rate was 39%.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…In Brazil, resistance to carbapenems in S. marcescens strains has rarely been reported and is associated exclusively with KPC-2 production (4,5,18). Outbreaks of S. marcescens infections in ICUs are frequently associated with considerable mortality rates, ranging from 14% to 60% (18,19). This observation is in accordance with our findings, as the overall mortality rate was 39%.…”
supporting
confidence: 91%
“…marcescens shows intrinsic resistance to several antimicrobial agents (3,17) and is capable of acquiring multiple drug resis- tance mechanisms during antimicrobial therapy (1,2). In Brazil, resistance to carbapenems in S. marcescens strains has rarely been reported and is associated exclusively with KPC-2 production (4,5,18). Outbreaks of S. marcescens infections in ICUs are frequently associated with considerable mortality rates, ranging from 14% to 60% (18,19).…”
mentioning
confidence: 99%
“…Results of PFGE of selected K. pneumoniae strains are shown in figure 3. Molecular typing of S. marcescens revealed 2 clusters, as reported elsewhere [16], and a previously unrecognized cluster involving 4 infants. Of the remaining 3 species-E. coli, P. aeruginosa, and E. cloacae-there were 2-4 previously unrecognized clusters per species.…”
Section: Isolates Associated With Infectionssupporting
confidence: 77%
“…From these pediatric nosocomial infection studies, many environmental sources or point sources have been found as reservoirs for S. marcescens, including hands of health care workers and exposure to health care workers (14,156,198,249,267,362,393,396,423), contaminated breast milk, formula, and breast pumps (133,156,204,274,393), contaminated parenteral nutrition (18), an infected neonate as the index patient or colonization of hospitalized infants (28,63,100,148,238,269,270,275,338,362,400), equipment such as incubators (28,198), laryngoscopes (95,204), suction tubes, soap dispensers (52), and waste jars (393), air conditioning ducts (387), contaminated hand brushes (7), contaminated disinfectants and soap (14,52,76,258,313,396), cotton wool pads (137), multidose nebulizer dropper bottles (215), and multidose medications (133).…”
Section: S Marcescensmentioning
confidence: 99%